2009
DOI: 10.3892/ijo_00000267
|View full text |Cite
|
Sign up to set email alerts
|

The MDM2 antagonist nutlin-3 sensitizes p53-null neuroblastoma cells to doxorubicin via E2F1 and TAp73

Abstract: Abstract. Neuroblastoma (NB) is a primitive neuroectodermal tumor and the second most common solid tumor in children. NB exhibits heterogeneous behavior and spontaneous regression can occur in patients under 12 months of age. Response to treatment is both age-and stage-specific; however, patients over 1 year of age are generally considered high risk. NB tumors from these patients are often characterized by alterations in p53 expression and murine double minute (MDM2) activity with concomitant resistance to che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…25,26 E2F-1 differs from that of other E2F family members due to its ability to regulate not only cell-cycle progression but also apoptosis as it directly induces the expression of p73, of caspase 3 and 7 and of some pro-apoptotic Bcl-2 family members. [27][28][29][30][31][32][33][34] We show here that E2F-1 is a major contributor of caspase-dependent induction of Noxa in response to ABT-737 treatment. Caspases cleave the E2F-1 regulator pRb in ABT-737-treated cells, giving rise to a p68Rb truncated form, which has a direct role in Noxa and cell death inductions together with E2F-1.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…25,26 E2F-1 differs from that of other E2F family members due to its ability to regulate not only cell-cycle progression but also apoptosis as it directly induces the expression of p73, of caspase 3 and 7 and of some pro-apoptotic Bcl-2 family members. [27][28][29][30][31][32][33][34] We show here that E2F-1 is a major contributor of caspase-dependent induction of Noxa in response to ABT-737 treatment. Caspases cleave the E2F-1 regulator pRb in ABT-737-treated cells, giving rise to a p68Rb truncated form, which has a direct role in Noxa and cell death inductions together with E2F-1.…”
mentioning
confidence: 52%
“…As treatment with the Mdm2 inhibitor Nutlin-3a was shown to enhance the pRb/E2F-1 pathway, 33,34 we reasoned that it may increase cell sensitivity to ABT-737, provided pRb is present. We found that combination of Nutlin-3a to ABT-737, but not treatment with anyone alone, induced dramatic cell death in the breast cancer cell lines MDA-MB-231 and MDA-MB-468, cells that carry p53 mutations (R280K and R273H, respectively) and constitutively express low levels of pRb (Figures 8a and b).…”
mentioning
confidence: 99%
“…Interestingly several groups have reported the activation of p53 responsive genes such as Puma and p21 and that Nutlin can act in effective synergy with chemotherapeutic drugs to induce apoptosis in p53 defective tumor cells. The effect seems to be linked to the activation of both E2F1 and p73 by nutlin treatment (Ambrosini et al 2007;Kitagawa et al 2008;Lau et al 2008;Peirce and Findley 2009). This in turn is consistent with evidence that Mdm2 binds to both these proteins using the amino-terminal interaction domain that binds to p53 and is blocked by Nutlin.…”
Section: P53-based Cancer Therapymentioning
confidence: 96%
“…Nevertheless, p73/MDM2 interaction is still sufficient to impede p73 transcriptional function. The p53 activator nutlin has been shown to activate p73 in cancer cells [18,19]. Nutlin treatment was shown to induce accumulation of p73 and transcription factor E2F1 with a subsequent induction of the p53-upregulated modulator of apoptosis -PUMA [19].…”
Section: Discussionmentioning
confidence: 99%
“…The p53 activator nutlin has been shown to activate p73 in cancer cells [18,19]. Nutlin treatment was shown to induce accumulation of p73 and transcription factor E2F1 with a subsequent induction of the p53-upregulated modulator of apoptosis -PUMA [19]. In the recent work Busuttil et al showed that induction of Bim by p73 accounts for the induction of p73-dependent apoptosis in activated T cells with chalcone-inhibited MDM2 [20].…”
Section: Discussionmentioning
confidence: 99%